ANALISIS PEMILIHAN SUPPLIER SPAREPART MOTOR PADA BENGKEL CV. AGUS MOTOR BATAM - Sirait, Ripaldo; Sirait, Ganda (Computer Science and Industrial Engineering, 2025)
Suppliers play an important role in providing quality products and in ensuring the availability of goods needed by the company. Supplier selection is a critical activity because the supplier will supply the company's raw materials in the long term so that it has a significant impact on the company's productivity. CV. Agus Motor is a motorcycle repair shop. The problems that often occur in CV. Agus Motor repair shops are delivery time, inconsistent quality, spare part prices, and warranties. This study aims to determine the right supplier of manual or automatic motorcycle chains at CV. Agus Motor. The methods used in this study are Analytical Hierarchy Process (AHP) and Topsis. From this study, the results obtained The most optimal supplier based on the calculation of the AHP method which is the first priority is the Cahaya Motor Batam supplier with a weight value of 0.603 and a percentage of 60.30%, the Surya Mega Teknik supplier is the second priority with a weight value of 0.232 and a percentage of 23.2%, and the Sarana Motor supplier is the third priority with a weight value of 0.164 and a percentage of 16.4%. And with the TOPSIS method, the first priority is Supplier Cahaya Motor Batam is a superior alternative with a value of 1,000, Supplier Surya Mega Teknik is the second priority with a value of 0.092, and Supplier Sarana Motor as the third priority with a value of 0.089. Therefore, the first alternative is selected, namely Cahaya Motor Batam to become a supplier for CV. Agus Motor.